2018
DOI: 10.2196/mhealth.9186
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Nomophobia Questionnaire in the Italian Language: Exploratory Factor Analysis

Abstract: BackgroundNomophobia, which is a neologism derived from the combination of “no mobile,” “phone,” and “phobia” is considered to be a modern situational phobia and indicates a fear of feeling disconnected.ObjectiveNo psychometric scales are available in Italian for investigating such a construct. We therefore planned a translation and validation study of the Nomophobia Questionnaire (NMP-Q), which is an instrument developed by Yildirim and Correia. Subjects were recruited via an online survey using a snowball ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
22

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 11 publications
4
57
0
22
Order By: Relevance
“…Our objective affirms that there is a relationship between Nomophobie and academic performance and we found that the massive use of mobile phone has an impact on academic performance among adolescents. A study by Adawi et al (2018) The NMP-Q translated from English to Italian had a Cronbach global alpha of 0.95. It is almost equal between the girl-boy type but this dependence on smartphones (Nomophobia) is more frequent among the pupils in the middle school and it increases according to the Age (r = .112 **, p < .009, but in the high school cycle we found the students of the 1st year high school who were touched by the Nomophobia compared to the other level (1st year bachelor and 2nd year bachelor) which is explained in these last levels (1st year bachelor and 2nd year bachelor) that the students are in a hurry by the courses and preparation for the final exams.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective affirms that there is a relationship between Nomophobie and academic performance and we found that the massive use of mobile phone has an impact on academic performance among adolescents. A study by Adawi et al (2018) The NMP-Q translated from English to Italian had a Cronbach global alpha of 0.95. It is almost equal between the girl-boy type but this dependence on smartphones (Nomophobia) is more frequent among the pupils in the middle school and it increases according to the Age (r = .112 **, p < .009, but in the high school cycle we found the students of the 1st year high school who were touched by the Nomophobia compared to the other level (1st year bachelor and 2nd year bachelor) which is explained in these last levels (1st year bachelor and 2nd year bachelor) that the students are in a hurry by the courses and preparation for the final exams.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the articles aimed at validating an instrument for measuring nomophobia stand out. They have adapted the tool proposed by Yildrim and Correia [24] to different country contexts, such as Iran [7], Spain [17,27,28], and Israel [14], reaffirming its factors of validity and reliability [12]. Some review articles were also included [17,38,65].…”
Section: Methodological Designmentioning
confidence: 99%
“…Most research has nomophobia as the main and only study variable [1,4,7,14,[17][18][19][22][23][24]27,28,30,31,34,65]. However, other researchers have been interested in examining the relationship between nomophobia and physical factors, such as age [29,33,60], context [29], presence of Carpal tunnel syndrome or median nerve in the wrist [61], and gender [32,33,35,39,58].…”
Section: Main Variablesmentioning
confidence: 99%
See 2 more Smart Citations